Independent videogames cultures, networks, techniques and politics - Ruffino, Paolo (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry - often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
OCLC-licensed vendor bibliographic record.
Keywords: Video games industry; Video games -- Design; Video games -- Social aspects; Video games industry -- Case studies; Video games -- Design -- Case studies; Video games -- Social aspects -- Case studies; SOCIAL SCIENCE / Media Studies